Mengajarkan Modernitas di Tengah Perubahan Interaksi Sosial dalam Film - Muthmainnah, Fitri (Journal of Religion and Film, 2023)
This article explores the dynamics of modernity through two main focuses, first, in the context of social interaction in the transformation of modernity, where social change is studied through shifts in relationships between individuals in the contemporary era. Through film analysis, this article investigates how social interaction is a key driver of change, shaping the new face of modern society. The second focus is the role of film as an educational medium, illustrating film's ability to convey the values of modernity in a deep and interesting way. By showing not only visuals of these changes, but also through complex narratives, films are able to stimulate critical thinking and form more diverse perspectives. Overall, this article provides a holistic insight into how modernity can be taught and absorbed in society, by involving changes in social interactions and the crucial role of film as an effective educational medium.